Feminismo negro e epistemologia social: trajetórias de vida de pesquisadoras negras em Biblioteconomia e Ciência da Informação - Silva, Leyde Klebia Rodrigues da (2020)
The goal of this research is to (re)tell the life trajectories of black researchers in the field of Librarianship and Information Science and their intellectual braids, based on the foundation of social epistemology. Specifically, it was intended: to discuss social epistemology as a theoretical basis for the analysis of life trajectories; to reflect on black feminism, feminist epistemologies, the debates and confrontations of black women in science; to narrate the trajectories of the leading black researchers from the selected bio-bibliographical sources; and to identify the intellectual braids of researchers in Librarianship and Information Science from the notion of Genealogical Baobab. Methodologically it was based on a qualitative approach research of documentary type. The selected sources, called biobibliographical, memorials and authorial articles made available by the research protagonists, were analyzed using the autobiographical method, the analytical principle of intersectionality, and understood from the perspective of a Black Feminist Social Epistemology. The intellectual braids were built from the notion of Genealogical Baobab, and from data collected on the Lattes Platform, via the Lattes Curriculum bases and the Research Groups Directory. Results show that the narrative fragments of the researchers' life trajectories along with their respective Genealogical Baobabs served as input for understanding the performance, experience, struggle, protagonism and resilience of these women in their spaces. In the final considerations, the importance of the presence of black women in all areas of society is reinforced, and although the media and school curricula do not address the depth of these existences, the complex lives of black women can promote great scientific contributions and important social transformations.